A Dense Metal–Organic Framework for Enhanced Magnetic Refrigeration. (1st July 2013) - Lorusso, Giulia; Sharples, Joseph W.; Palacios, Elias; Roubeau, Olivier; Brechin, Euan K.; Sessoli, Roberta; Rossin, Andrea; Tuna, Floriana; McInnes, Eric J. L.; Collison, David; Evangelisti, Marco
<x xml:space="preserve">Abstract</x> The three‐dimensional metal–organic framework Gd(HCOO)3 is characterized by a relatively compact crystal lattice of weakly interacting Gd3+ spin centers interconnected via lightweight formate ligands, overall providing a remarkably large magnetic:non‐magnetic elemental weight ratio. The resulting magnetocaloric effect per unit volume is decidedly superior in Gd(HCOO)3 than in the best known magnetic refrigerant materials for liquid‐helium temperatures and low‐moderate applied fields. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>